Tantangan dan Kesempatan Praktisi Public Relations Menghadapi Dinamika Era Digital di Indonesia - Nurul Jannati Rochmah (Universitas Al Azhar Indonesia, 2015)
n Indonesia, the impact of internet development which is characterized by the surging internet users in the country reached 88.1 million people, has been forcing PR pro fessionals to be able to master the technique of imaging through various online media plat forms. They demand not only media relations skill, but also master the technology of the In ternet and communication via various online platforms. It’s intended to strip the challenges and opportunities of public relations practitioners in facing the dynamics of the digital era in Indonesia, and the conclusion are the digital world in Indonesia is an ideal means for Practitioners PR to conduct his homework by targeting young people and workers. Addi tionally, social media is the most effective online platform to touch these circles. Thus, to captivate internet users in Indonesia, Indonesia PR practitioners must master at least five basic tools that include website Online PR; Online press releases; e-newsletter; blog; as well as social media. Furthermore, PR practitioners are also required to be able to optimize the Internet as a PR new media because of a convergence that runs between the PR and the digital era can build profits as well as new opportunities for the company.